Self Defense Mechanism as an Overcoming Tool of Anxiety in the Novel Me Before You - Terry Angela Monica; jepri jepri; Ulum Janah (Prologue: Journal on Language and Literature, 2020)
This research focuses on the psychology of a character in the novel Me Before You by Jojo Moyes. There are two objectives in this study; 1). To find out the types of anxiety experienced by the character in the novel Me Before You by Jojo Moyes and; 2). To explain how self-defense mechanism works to overcome anxiety in the novel Me Before You by Jojo Moyes. This study uses Sigmund Freud's psychoanalysis theory regarding anxiety and defense mechanism; the methodology employed is qualitative research in which the researcher tried to present the issues descriptively. The main data sources in this study were taken from the form of dialogs, descriptions, and sentences contained in the novel Me Before You by Jojo Moyes. The results of this study, the researcher concluded that there were three types of anxiety experienced by the character in the novel Me Before You by Jojo Moyes, namely neurotic, moral and realistic anxiety. To overcome this anxiety the character uses four types of defense mechanisms namely displacement, reaction formation, rationalization, and sublimation. The most effective type of self-defense mechanism to overcome the anxieties that arise in character is rationalization because an individual where the reality that is lived is all based on logic and rationality.